2012
DOI: 10.2139/ssrn.2054066
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Job Satisfaction and Firm Value, with Implications for Corporate Social Responsibility

Abstract: Executive OverviewHow are job satisfaction and firm value linked? I tackle this long-standing management question using a new methodology from finance. I study the effect on firm-level value, rather than employee-level productivity, to take into account the cost of increasing job satisfaction. To address reverse causality, I measure firm value by using future stock returns, controlling for risk, firm characteristics, industry performance, and outliers. Companies listed in the "100 Best Companies to Work For in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 92 publications
2
56
1
Order By: Relevance
“…Adm. Pública -Rio de Janeiro 47(6):1477-496, nov./dez. 2013 Edmans (2012) evaluated the links between work satisfaction and firm value instead of focusing on the link between work satisfaction and individual job performance. After analyzing the 100 best companies to work in America, the author concluded that, consistent with organizational behavior literature, work satisfaction is beneficial for firm value since it is directly related to the financial outcomes of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adm. Pública -Rio de Janeiro 47(6):1477-496, nov./dez. 2013 Edmans (2012) evaluated the links between work satisfaction and firm value instead of focusing on the link between work satisfaction and individual job performance. After analyzing the 100 best companies to work in America, the author concluded that, consistent with organizational behavior literature, work satisfaction is beneficial for firm value since it is directly related to the financial outcomes of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Saari and Judge (2004), the relationship between job satisfaction and organisational outcomes is widely studied in the literature. Edmans (2012) noted that job satisfaction has implications for recruitment, retention, motivation, and other HRM practices. Referring to Landy (1989), Edmans (2012) further argued that job satisfaction is likely to improve employee recruitment, retention, and motivation, which in turn may improve profits, new product development and positive customer ratings.…”
Section: Cultural Job Satisfaction and International Related Performancementioning
confidence: 99%
“…A recent meta-analysis found that higher employee job satisfaction relates to higher customer satisfaction (Mendoza & Maldonado, 2014). Employees with more job satisfaction also perform better at work (Davar & Bala, 2012), have more organisational commitments (Magnini et al, 2011), less likelihood of turnover intention (Chen et al, 2015), and positively link to perceived organisational value (Edmans, 2012). Furthermore, higher job satisfaction is involved in lower work-to-family conflict (Chen et al, 2015), more subjective well-being like life satisfaction, happiness (Halkos & Bousinakis, 2010).…”
Section: Job Satisfactionmentioning
confidence: 99%